Performing Ideologies: Fostering Raciolinguistic Literacies Through Role‐Play in a High School English Classroom. Issue 2 (12th March 2019) - Seltzer, Kate
Abstract: The author describes a literacy activity that took place in an 11th‐grade English language arts classroom: student‐created role‐play. Through a discussion of two such role‐plays, the author explores how these performances illustrate students' engagement with raciolinguistic ideologies that marginalize certain speakers through the simultaneous processes of being seen and heard through deficit perspectives. Students collaboratively designed role‐plays that demonstrated their understandings of how their language practices were (mis)heard by linguistic gatekeepers. In analyzing these performances, the author shows how students creatively represented their grapplings with raciolinguistic ideologies and the white listening subjects who maintain them. The author discusses how educators can take a critical translingual approach to language and literacy classrooms, encouraging students—through multilingual, multimodal texts, writing assignments, and activities such as role‐play—to interrogate and disrupt such oppressive ideologies.